How are media utilized for Productive Skills Instructions amidst online learning? Evidence from Indonesian EFL Lecturers - Azizah Maulina Erzad; Rudi Hartono; Puji Astuti; Widhiyanto Widhiyanto (Universitas Negeri Semarang, 2022)
The teaching and learning process has changed from in-person instruction to online learning during the Covid 19 outbreak. EFL lecturers should utilize a variety of media for teaching English, particularly for instruction on productive skills. The paper aims to investigate the Indonesian EFL lecturers’ views on utilizing media for English productive skills instructions amidst online learning. This study emphasized the implementation of the media for teaching productive skills, how to assess students' productive skills, how students' motivation during online learning, and students' ability to use clause complexes in English productive skills. This research relied on a qualitative study. A structured questionnaire was employed to collect the data. Eight lecturers from several universities contributed the information as research data. The current study yielded a range of findings. First, various media were employed for synchronous and asynchronous learning in order to discuss the teaching materials, give quizzes, and submit students’ assignments. Second, assessments for speaking instruction were conducted through students’ performances utilizing video conferencing tools, but assessments for writing instruction were conducted through asynchronous learning using Google Classroom or the university's LMS. Third, during online learning, students have less motivation in productive skills classes and their ability to use clause complexes in productive skills is decreasing.